Analisis Rantai Pasok dan Nilai Tambah Kopi (Studi Kasus di CV Kiniko Nagari Tabek Patah Kecamatan Salimpaung Kabupaten Tanah Datar) Supply Chain Analysis and Value Added of Coffee (Study Case at CV Kiniko Nagari Tabek Patah Salimpaung District Tanah Datar Regency) - Sebayang, Aulia Shafira; Hamzah, Farida Hanum; Restuhadi, Fajar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
The purpose of this research was to identify the coffee supply chain, value added analysis received by the supply chain actors, and arrange alternative strategies by evaluating the internal and external factors to determine strategic priorities for CV Kiniko development. This study used descriptive quantitative and qualitative method. Descriptive qualitative used to describe the coffee supply chain using Vorst’s framework for chain design and set alternative strategies for CV Kiniko development by the internal factors evaluation and external factors evaluation matrix using SWOT analysis and rating the strategic priorities for CV Kiniko development using analytical hierarchy process (AHP). Descriptive quantitative used for measuring value added using Hayami method. The coffee supply chain started from the coffee farmers, coffee middleman, CV Kiniko, distributor and sales. The value added ratio of the actors as follow: coffee farmers 32% (medium value added ratio category), coffee middleman 4% (low value added ratio category) and CV Kiniko 55% (high value added ratio category). The strategic priorities that CV Kiniko has to do to improve the value added is expand the marketing networks by using the development of technology and information (0.358). Keywords: coffee, supply chain, value added, SWOT, AHP